Energy Poverty Indicators in Ukraine: Definition and Statistical Assessment - Ogay, М. Yu. (Statistics of Ukraine, 2021)
An important step on the way to setting up a socio-economic trajectory of the national economy development in the context of Eurointegration process and to achieving a stable energy support of social needs is the approval and implementation of the Energy Security Strategy of Ukraine, being now under consideration of the Cabinet of Ministers of Ukraine. A strategic goal of the Strategy is defined as the guaranteed accessibility of energy sources and energy resources for all the types of consumers. However, given the rapidly declining standard of living, the government policy aimed at increasing energy tariffs has led to the increased share of households unable to meet their basic energy needs. The inability of households to meet their basic needs (to heat dwelling facilities in winter or to pay the bills) due to poor assess to energy services is defined in EU countries as energy poverty. In practice, determining the energy poverty includes the assessment of the share of total household or individual income spent for energy sources. But this share is not fixed by the Energy Community or the European Union, neither unified methodological approaches to determining vulnerable categories of population nor factors of energy poverty do exist, which highlights the topicality of this study. The conditions and standard of living of Ukrainian households are analyzed in view of their belonging to energy vulnerable ones. An assessment of basic features of households is made, to characterize the condition of housing stock and the modernization of housing; the availability of modern electric devices; the parameters of heating and cooling facilities; the parameters of water boiling facilities; the material condition of households and the structure of their total spending; the solvency of households. The information base for this study is the data obtained from the national sample survey on the accessibility and use of energy by Ukrainian households, held in 2019 on line on the USAID Project of Energy Security by the initiative of the State Statistics Service of Ukraine. The results of the study were summed up to build a set of indicators designed to provide a comprehensive picture of the main factors provoking energy poverty in Ukraine. It is argued that further use of the proposed method will enable for the adequate assessment of the scales and the depth of the energy poverty of Ukrainian households for elaborating effective measures to protect vulnerable population strata. It also emphasized that regular monitoring of energy poverty cannot be implemented with a reliable database that is yet to be created in Ukraine.